2009
DOI: 10.1103/physrevb.79.115132
|View full text |Cite
|
Sign up to set email alerts
|

Field-dependent mass enhancement inPr1xLaxOs4Sb12

Abstract: The scattering of conduction electrons by crystalline electric field (CEF) excitations may enhance their effective quasiparticle mass similar to scattering from phonons. A wellknown example is Pr metal where the isotropic exchange scattering from inelastic singlet-singlet excitations causes the mass enhancement. An analogous mechanism may be at work in the skutterudite compounds Pr1−xLaxOs4Sb12 where close to x=1 the compound develops heavy quasiparticles with a large specific heat γ. There the low lying CEF s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…19,20) It has been recently shown that the key to the formation of heavy quasiparticles excitations lies in the crystalline electric field (CEF) splitting of the J = 4 multiplet and that the heavy quasiparticle mass is related to the inelastic scattering processes of the conduction electrons. 22,23) This picture is supported by the observation of an anti-correlation between CEF splitting and effective mass. The concept of mass enhancement due to CEF excitations has been previously applied to Pr metal using the isotropic dipolar exchange interaction H ex .…”
Section: Introductionsupporting
confidence: 62%
See 2 more Smart Citations
“…19,20) It has been recently shown that the key to the formation of heavy quasiparticles excitations lies in the crystalline electric field (CEF) splitting of the J = 4 multiplet and that the heavy quasiparticle mass is related to the inelastic scattering processes of the conduction electrons. 22,23) This picture is supported by the observation of an anti-correlation between CEF splitting and effective mass. The concept of mass enhancement due to CEF excitations has been previously applied to Pr metal using the isotropic dipolar exchange interaction H ex .…”
Section: Introductionsupporting
confidence: 62%
“…As the divergence follows directly from the general analytic structure of the corresponding electron self energy it persists also in the self consistent solution for finite band width. 23) In concentrated systems the singlet-triplet excitations have a pronounced dispersion 62) and an applied field of critical strength therefore leads to a softening of ωq only in the restricted phase space around the AFQ ordering vector Q. Consequently the mass renormalization will be finite even at the critical field h c for AFQ order when ω Q =0.…”
Section: Is There a Field-induced Kondo Effect For Non-kramersmentioning
confidence: 99%
See 1 more Smart Citation
“…Itinerant quadrupolar excitations (quadrupolar excitons) have been suggested as mechanisms for heavy-fermion behavior and Cooper-pair binding in superconducting PrOs 4 Sb 12 [35][36][37]. They are not themselves magnetic, but aspherical conduction-electron scattering [38,39] together with charge-spin correlations in the conduction band might lead to interference effects in, and suppression of, the µ + -4f indirect interaction. We note that 10-15 K is also the temperature range below which the susceptibilities begin to diverge with increasing Nd concentration (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…10 It has been proposed 11,12 that low-energy crystalline electric field ͑CEF͒ excitations play an important role in the formation of Cooper pairs and likewise in the quasiparticle mass enhancement. 13,14 These only slightly dispersive excitations were identified in inelastic neutron-scattering ͑INS͒ experiments 15 in PrOs 4 Sb 12 . Furthermore NMR/ nuclear quadrupole resonance 16 and ultrasonic 17,18 measurements give evidence for the importance of anharmonic "rattling" oscillations of 4f-host ions in the cages formed by surrounding Sb 12 icosahedrons on the low-temperature properties.…”
Section: Introductionmentioning
confidence: 94%